FORMATION AND DEVELOPMENT OF MYTHICO-PHILOSOPHY THINKING (TASAWUF FALSAFI) - Tongat Tongat (Proceeding International Seminar of Islamic Studies, 2021)
Sufism is purifying the heart from dealing with other beings, abandoning natural qualities, suppressing human qualities, avoiding physical temptations, taking on various spiritual qualities, reminding oneself of the natural sciences, truly believing in God and following the prophetic law. Muhammad, PBUH. Meanwhile, Al-Qusyairi stated that Sufism is taking the essence and giving up everything that creatures have.Al Kattani said that Sufism is morals, that is, leaving bad things behind and being decorated with the main things. Sufism emphasizes the state of mind and soul as well as outward behavior in worshiping submission to Allah Almighty. Other understandings of Sufism seem to seek knowledge of reality, enlightenment, or gnosis (ma'rifat). Meanwhile, the way to reach ma'rifat to Allah SWT. in Sufism it is called tarekat which means the way to Allah SWT. Meanwhile, people who take the tarekat to reach Allah SWT. called salik and likened to a traveler. Therefore, the tarekat is an integral part of Sufism activities that develops a distinctive educational system in which inner issues are the most dominant activity. In subsequent developments, the word Sufism can also be interpreted specifically as a spiritual path (tarekat). This is essentially a practical method of guiding a person in a particular way of thinking, feeling and acting.Then came a Sufi figure named Al-Ghazali, he saw the conflict wanted to immediately reduce the conflict. Al-Ghazali only fully accepts Sufism based on the Koran and hadith and aims at a simple life, purification of the soul and moral cultivation. On the other hand, he gave sharp criticism to philosophers, such as the Mu'tazilah and Batiniyah. And finally Al-Ghazali succeeded in introducing the principles of moderate Sufism. So that in this century philosophical Sufism began to sink. The history of the development of philosophical Sufism reappeared in the 6th century Hijriyah. Keyword: Development, Thought, Philosopy